2007
DOI: 10.1152/ajpgi.00476.2006
|View full text |Cite
|
Sign up to set email alerts
|

The impact of continuous positive airway pressure on the lower esophageal sphincter

Abstract: The lower esophageal sphincter (LES) is the primary barrier to gastroesophageal reflux. Reflux is associated with periods of LES relaxation, as occurs during swallowing. Continuous positive airway pressure (CPAP) has been shown to reduce reflux in individuals with and without sleep apnea, by an unknown mechanism. The aim of this study was to determine the effect of CPAP on swallow-induced LES relaxation. Measurements were made in 10 healthy, awake, supine individuals. Esophageal (Pes), LES (Ples), gastric (Pg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 25 publications
(33 reference statements)
6
41
3
Order By: Relevance
“…4 However, in this current investigation, the use of GER medications, GER symptoms and nighttime-related GER symptoms, predicted aerophagia with CPAP use. Furthermore, a subset of 127 patients completed the same questionnaire before initiating CPAP therapy and individuals with preexisting GER symptoms were not more likely to develop aerophagia while on CPAP; thus the authors concluded that aerophagia may actually precipitate GER.…”
Section: O M M E N T a R Ycontrasting
confidence: 53%
“…4 However, in this current investigation, the use of GER medications, GER symptoms and nighttime-related GER symptoms, predicted aerophagia with CPAP use. Furthermore, a subset of 127 patients completed the same questionnaire before initiating CPAP therapy and individuals with preexisting GER symptoms were not more likely to develop aerophagia while on CPAP; thus the authors concluded that aerophagia may actually precipitate GER.…”
Section: O M M E N T a R Ycontrasting
confidence: 53%
“…GERD has been closely linked with IPF and OSA. Prior studies 35 have shown improvement in patients with GERD by treating the OSA with CPAP. Treating OSA with CPAP may simultaneously treat GERD in the patient with IPF, which may play a role in disease progression.…”
Section: Discussionmentioning
confidence: 98%
“…Potential mechanisms by which CPAP could reduce reflux include its effects on LES pressure or function, with previous studies showing an increase in LES pressure with CPAP application [19,20].…”
Section: Introductionmentioning
confidence: 99%